The Upcoming Four Trillion Dollar Infrastructure Gold Rush - Bryane Michael (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The largest 25 emerging markets (by population size) will need to make about four trillion dollars worth of investments by 2020. What does this mean for investors looking to cash in on the boom in government (and hopefully private) spending on infrastructure? Which markets will generate the most revenues for large international and domestic engineering and construction companies? How can investors profit from this 4 trillion “gold rush”? In this brief, we identify the global “design firms” and local construction and engineering companies based in emerging markets which will benefit most. We also provide five recommendations for improving the rate of return these companies can earn from this infrastructure boom. Such recommendations include lobbying for the full implementation of the WTO Agreement on Public Procurement (particularly in emerging markets), directly investment at emerging market infrastructure companies, securitizing and investing in water and transport companies, increasing the scope of services provided during master-planning projects and selling equity in infrastructure more widely in developing markets.
Keywords: G18; H54; 330; infrastructure; emerging markets; Infrastructure investment; Emerging economies